Impact of equity models and statistical measures on interpretations of educational reform - Idaykis Rodriguez (American Physical Society, 2012)
We present three models of equity and show how these, along with the statistical measures used to evaluate results, impact interpretation of equity in education reform. Equity can be defined and interpreted in many ways. Most equity education reform research strives to achieve equity by closing achievement gaps between groups. An example is given by the study by Lorenzo et al. that shows that interactive engagement methods lead to increased gender equity. In this paper, we reexamine the results of Lorenzo et al. through three models of equity. We find that interpretation of the results strongly depends on the model of equity chosen. Further, we argue that researchers must explicitly state their model of equity as well as use effect size measurements to promote clarity in education reform.